Impact of Body Mass Index on Static Postural Control in Adults With and Without Diabetes: A Cross-Sectional Study - Yin, Lianhua; Qin, Jiawei; Chen, Yannan; Xie, Jinjin; Hong, Cuiping; Huang, Jia; Xu, Ying; Liu, Zhizhen; Tao, Jing (Frontiers in Endocrinology, 2021)
Aim The objective of this research are to determine the intra-group and inter-group static balance differences measured from a force platform between T2DM and control groups stratified by BMI category. This research also explore the relationship of BMI and static balance performance. Methods We recruited 706 participants with T2DM and the other 692 healthy controls was sufficiently matched for age, gender, and BMI in this cross-sectional study. The participants were stratified into three groups by BMI: normal weight, overweight, and obesity. All participants performed two-legged static stance balance assessment on a firm force platform. The center of pressure (CoP) parameters were collected under eyes-open and eyes-closed conditions. Mann-Whitney U test was used to compare the static balance parameters within each BMI category in both groups. The static balance parameters among different weight groups were compared by Kruskal-Wallis test, post hoc pair-wise comparison were conducted. General linear model was conducted to examine the association between BMI and static balance parameters while controlling for confounding factors. Results Normal control group had statistical difference in most CoP parameters compared to T2DM group based on BMI category. Normal weight participants presented significant difference compared with overweight and/or obesity for total track length (TTL) and velocity of CoP displacements in Y direction (V-Y) under eyes-open condition, and for most CoP parameters under eyes-closed condition in both groups. There were statistically significant correlations between BMI and most static balance parameters under only eyes-closed condition according to the result of general linear model. Conclusion T2DM patients had impaired static balance performance compared to healthy controls at all BMI category. The findings also indicated the association between BMI and static balance, higher BMI individuals showed more static postural instability in both T2DM and healthy controls.